Persepsi Masyarakat Muslim Kelurahan Inderalaya OI Terhadap Materi Kampanye Dalam Pilkada 2020 - Haryani, Duwi; Syukri, Ahmad; Mikail, Kiki (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
ABSTRACT The General Election of Regional Head and Deputy Regional Head of Ogan Ilir Regency 2020-2025 has been held on December 9, 2020 which is a form of democracy where all people in Ogan Ilir Regency have the right to choose their own leader directly. In the 2020 post-conflict local election, 2 candidates for regent and deputy regent were participated, where the 2 candidates were Panca Wijaya Akbar Mawardi-Ardani and Ilyas Panji Alam-Endang PU Ishak. Of the two pairs of candidates during the campaign period, they traveled from village to village to convey their vision, mission and superior work program to the people of Ogan Ilir Regency, including Indralaya Raya Village. This research is interesting because the post-conflict local election which was held in 2020 brought together newcomers, namely the younger brother of Ovi, the Ilyas couple, in the last election and the incumbent will be the hottest arena for political contestation in South Sumatra and the focus of this research is the Muslim community. This study aims to determine the political perception of the Muslim community towards the campaign material for the candidate pair for regent and deputy regent Ogan Ilir in the 2020 post-conflict local election and the factors that influence this political perception. This type of research is quantitative research which is expressed by numbers. The method used is a questionnaire/questionnaire method, interviews and literature as supporting data in this study. The technique of taking respondents in this research is purposive sampling with a total of 286 respondents according to the research criteria. This study uses descriptive statistical analysis. The results of this study are the emergence of political perceptions of the Muslim community in Indralaya Raya Village towards the campaign material for the candidate pair for the regent of Ogan Ilir in the 2020 post-conflict local election, considering that the post-conflict local election is 100% important, the public also knows who the candidate for regent is 97.7%. In terms of the campaign issues carried out by the two pairs of candidates, the average Muslim community in Indralaya Raya Sub-district had participated in 90.7%, the Indralaya Raya village community itself listened more to the campaign material for the regent candidate only through explanations from the family of 60.5%. They also have their own opinion about who is the most attractive during their campaign period 62.8% and the most convincing them to vote for them is 60.5%. Respondents chose serial number 1 Panca-Ardani because from their explanation there were several factors that influenced them to choose serial number 1, namely: internal factors exist within each individual such as a person's ability to accept and process influences from outside and external factors from external characteristics such as the characteristics of the objects involved, such as size, color, uniqueness and the movement of other objects. What is meant by objects here are banners, billboards and posters. Public perception arises because of the influence factor from within the voters themselves as well as external factors. The perception of the Muslim community in Indralaya Raya Village only focuses on the campaign materials brought by the candidates for regional heads and the factors that influence people's perceptions of choosing their regional head candidates. Keywords: Campaign Material, Muslim Community, Ogan Ilir, Regional Head Election, Political Perception ABSTRAK Pemilihan Umum Kepala Daerah dan Wakil Kepala Daerah Kabupatan Ogan Ilir 2020-2025 ini telah dilaksanakan pada tanggal 9 Desember 2020 yang merupakan wujud demokrasi dimana semua masyarakat di Kabupaten Ogan Ilir memiliki hak untuk memilih sendiri pemimpinnya secara langsung. Dalam pemilukada tahun 2020 lalu diikuti oleh 2 calon bupati dan wakil bupati, dimana 2 calon tersebut adalah Panca Wijaya Akbar Mawardi-Ardani dan Ilyas Panji Alam-Endang PU Ishak. Dari kedua pasangan calon tersbeut selama masa kampanye diadakan mereka berkeliling dari desa ke desa untuk menyampaikan visi misi serta program kerja unggulannya kepada masyarakat Kabupaten Ogan Ilir tak terkecuali di Kelurahan Indralaya Raya. Penelitian ini menjadi menarik karena pemilukada yang telah dilaksanakan pada tahun 2020 mempertemukan antara pendatang baru yakni adik dari Ovi pasangan Ilyas dipemilukada periode lalu dan incumbent ini akan menjadi ajang kontestasi politik di Sumatera Selatan yang terpanas dan yang menjadi focus penelitian ini adalah masyarakat muslim. Penelitian ini bertujuan untuk mengetahui persepsi politik masyarakat muslim terhadap materi kampanye pasangan calon bupati dan wakil bupati Ogan Ilir pada pemilukada tahun 2020 dan faktor-faktor yang mempengaruhi dari persepsi politik tersebut. Jenis penelitian ini adalah penelitian kuantitatif yang dinyatakan dengan angka-angka. Metode yang digunakan adalah metode angket/kuesioner, wawancara dan literature sebagai data pendukung dalam penelitian ini. Teknik pengambilan responden dalam penelitian ini yakni purposive sampling dengan jumlah responden 286 responden yang sesuai dengan kriteria penelitian. Penelitian ini menggunakan analisis statistik deskriptif. Hasil dari penelitian ini adalah timbulnya persepsi politik masyarakat muslim di Kelurahan Indralaya Raya terhadap materi kampanye pasangan calon bupati Ogan Ilir pada pemilukada tahun 2020, menganggap pemilukada itu penting 100%, masyarakat juga mengetahui siapa saja calon bupatinya 97.7%. Untuk masalah kampanye yang dilakukan oleh kedua paslon rata-rata masyarakat muslim di Kelurahan Indralaya Raya pernah mengikutinya 90.7%, masyarakat kelurahan Indralaya Raya sendiri lebih banyak mendengarkan materi kampanye calon bupatinya hanya lewat penjelasan dari keluarga 60.5%. Mereka juga memiliki pendapat masing-masing tentang siapa yang paling menarik dalam masa kampanye mereka 62.8% dan paling meyakinkan mereka untuk mereka pilih 60.5%. Responden memilih pasangan no urut 1 Panca-Ardani karena dari penjelesan mereka ada beberapa faktor yang mempengaruhi mereka untuk memilih no urut 1, yakni : faktor internal terdapat dalam diri setiap individu seperti daya pilih seseorang untuk menerima dan mengolah pengaruh dari luar dan eksternal itu faktor dari luar seperti karakteristik dari objek yang terlibat misalnya ukurun, warna, keunikan serta gerakan objek lainnya. Yang dimaksud objek disini adalah banner, baliho dan poster. Persepsi masyarakat timbul karena adanya faktor pengaruh dari dalam diri pemilih itu sendiri serta faktor dari luar. Persepsi masyarakat muslim di Kelurahan Indralaya Raya hanya terfokus pada materi kampanye yang dibawakan para calon kepala daerah serta faktor yang mempengaruhi persepsi masyarakat memilih calon kepala daerahnya. Kata Kunci : Materi Kampanye, Masyarakat Muslim, Ogan Ilir, Pemilukada, Persepsi Politik